Distance and Online Learning Solutions in the Context of Modern Legal Educational Policy - Stepanenko, Raviya Faritovna; Ainoutdinova, Irina Nailjevna; Krotkova, Natalya Viktorovna (Cuestiones Políticas, 2020)
The objective of this article is the best strategies and models of distance and online education to universities in the context of modern legal education policy, tempting its effectiveness. The methodological framework of this research is based on the comparative anective of distance and online education best practices offered by some universities around the world. A full study of the technical, pedagogical and managements issus of distance education has also been provided. Based on an empirical approach, testing, evaluation and control of usability, accessibility, file and security of some techniques, and related resources have been carried out. An experimental study has also been conducted with the aim of obtaining, comparing and using certain relevant data on the attitudes, priorities and learning outcomes of law students in a traditional versus distance learning environment. The main result of the study is the design of a model of mass, open and lively distance learning and teaching that enhances the quality of university education in general and the training of law students in particular.